Thermally stable composition, polymer material composition, and preparation method and application thereof

The problem of insufficient thermal stability of the material is solved by using a combination of bimetallic complex with specific structures in PVC or CPVC materials, and higher thermal stability and lower thermal stability are achieved energy consumption.

CN119431886APending Publication Date: 2025-02-14NORTHERN RARE EARTH RUIHONG (BAOTOU) NEW MATERIALS TECHNOLOGY CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411713139.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing PVC or CPVC materials are prone to dechlorination during processing, resulting in insufficient thermal stability, and commonly used calcium and zinc and rare earth thermal stabilizers have problems such as poor compatibility and limited thermal stability.

Method used

The thermal stabilization composition including 0.5 to 2 parts by weight of the bimetal complex, 0.05 to 1 part by weight of the antioxidant, 0.5 to 2 parts by weight of the lubricant, and 0.1 to 0.9 parts by weight of the auxiliary stabilizer, is adopted to pass through the center of the bimetal complex. The atoms are rare earth elements and transition metal elements. The ligand is shown in formula (I), combining antioxidants, lubricants and auxiliary stabilizers to improve the thermal stability of the polymer material.

Benefits of technology

It significantly improves the thermal stability of polymer materials, has a smaller balance torque, reduces energy consumption during processing, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156249480000021
    Figure BDA0005156249480000021
  • Figure BDA0005156249480000041
    Figure BDA0005156249480000041
  • Figure BDA0005156249480000061
    Figure BDA0005156249480000061
Patent Text Reader

Abstract

The invention discloses a thermostable composition, a polymer material composition and a preparation method and application thereof. The thermostable composition provided by the invention comprises 0.5-2 parts by weight of a bimetallic complex, 0.05-1 part by weight of an antioxidant, 0.5-2 parts by weight of a lubricant and 0.1-0.9 part by weight of an auxiliary stabilizer, central atoms of the bimetallic complex are rare earth elements and transition metal elements, and a ligand of the bimetallic complex is alkyl dithiocarbamate; the transition metal element is selected from one or more of aluminum, zinc, magnesium, tin and nickel; the auxiliary stabilizer is selected from one or more of phosphite ester, dipentaerythritol ester, epoxidized soybean oil, dibutyl maleate, dibenzoylmethane and hydrotalcite. The heat stabilizer can effectively improve the heat stability of a polymer material, and has relatively small balance torque.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heat-stable composition, a polymer material composition, a preparation method and application thereof. Background Art

[0002] PVC or CPVC has excellent performance and low price, and has a wide range of applications in various fields. PVC or CPVC is easily dechlorinated and degraded during processing, so a heat stabilizer needs to be added. For example, CN116355328A discloses a heat-resistant and oxidation-resistant PVC particle composition, including polyvinyl chloride, nitrile rubber, silicone rubber, filler, heat stabilizer, colorant, liquid paraffin, plasticizer, calcium sulfate whisker, and antioxidant. The heat stabilizer is a calcium zinc stabilizer or a rare earth stabilizer, and the specific selection of the stabilizer is not disclosed. Calcium zinc heat stabilizers have limited thermal stability, and the product itself is mostly compounded by small molecule materials, which are easy to precipitate during production, and the thermal stability in the later stage is insufficient. Rare earth stabilizers are mostly inorganic substances, which have poor compatibility with PVC and affect thermal stability.

[0003] CN104725432B discloses a diethyldithiocarbamate-based rare earth-transition metal bimetallic complex, the general structural formula of which is Ln x B y (DDTC) z , where: Ln represents one of lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium; B represents one of cobalt, nickel, copper, and zinc metal elements; DDTC is a diethyldithiocarbamate ion. CN109233029A discloses a rare earth-transition metal rubber vulcanization accelerator masterbatch, which is composed of an accelerator, an antioxidant, styrene-butadiene rubber, sulfur, zinc oxide, and stearic acid. The accelerator includes a dimethyldithioaminoacid formic acid rare earth-transition metal complex, a diethyldithioaminoacid formic acid rare earth-transition metal complex, a dibutyldithioaminoacid formic acid rare earth-transition metal complex, and a dibenzyldithioaminoacid formic acid rare earth-transition metal complex. The rare earth element is 16 lanthanide elements excluding promethium, and the transition metal is one of metal elements such as cobalt, nickel, copper, and zinc. In the above prior art, the diethyldithiocarbamate-based rare earth-transition metal bimetallic complex is used as a vulcanization accelerator. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a thermally stable composition, which can effectively improve the thermal stability of polymer materials and has a small equilibrium torque.

[0005] Another object of the present invention is to provide a method for preparing a heat-stable composition, wherein the heat-stable composition obtained by the preparation method can effectively improve the thermal stability of polymer materials and has a small equilibrium torque.

[0006] Another object of the present invention is to provide a use of the heat-stable composition.

[0007] Another object of the present invention is to provide a polymer material composition, which has high thermal stability and low energy consumption during production. Another object of the present invention is to provide a method for preparing the polymer material composition.

[0008] The above purpose is achieved through the following technical solutions.

[0009] In one aspect, the present invention provides a thermally stable composition comprising 0.5 to 2 parts by weight of a bimetallic complex, 0.05 to 1 parts by weight of an antioxidant, 0.5 to 2 parts by weight of a lubricant, and 0.1 to 0.9 parts by weight of an auxiliary stabilizer;

[0010] The central atoms of the bimetallic complex are rare earth elements and transition metal elements, and the ligands of the bimetallic complex are as shown in formula (I);

[0011] The transition metal element is selected from one or more of aluminum, zinc, magnesium, tin and nickel;

[0012]

[0013] Wherein, R1 and R2 are independently selected from C1 to C6 alkyl groups;

[0014] The auxiliary stabilizer is selected from one or more of phosphites, dipentaerythritol esters, epoxy soybean oil, dibutyl maleate, dibenzoylmethane, and hydrotalcite.

[0015] According to the heat-stable composition of the present invention, preferably, the rare earth element is selected from one or more of lanthanum, neodymium, europium and ytterbium.

[0016] According to the heat-stable composition of the present invention, preferably, the central atom is selected from one of the following compositions:

[0017] (A) lanthanum and aluminum;

[0018] (B) Neodymium and magnesium;

[0019] (C) europium and nickel;

[0020] (D) lanthanum and zinc;

[0021] (E) Ytterbium and tin.

[0022] According to the heat-stabilizing composition of the present invention, preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 215, antioxidant 168, antioxidant 1076, antioxidant 5057, antioxidant 626, and antioxidant DLTP;

[0023] The lubricant is selected from one or more of stearic acid, polyethylene wax, oxidized polyethylene wax, Fischer-Tropsch wax, and monoglyceride.

[0024] In another aspect, the present invention provides a method for preparing the above-mentioned thermally stable composition, comprising the following steps:

[0025] The dual metal complex, antioxidant, lubricant and auxiliary stabilizer are mixed to obtain a heat-stable composition.

[0026] According to the preparation method of the present invention, preferably, the following steps are further included: reacting a solution containing a rare earth element source, a transition metal element source and a ligand source under the conditions of an initial reaction system pH of 6 to 9 and a temperature of 45 to 80° C. to obtain a bimetallic complex;

[0027] Wherein, the anion in the ligand source is as shown in formula (II):

[0028]

[0029] In formula (II), R3 and R4 are independently selected from C1 to C6 alkyl groups;

[0030] The molar ratio of the rare earth element in the rare earth element source, the transition metal element in the transition metal element source, and the ligand source is 1:(0.5-2):(3 / N-7 / N); wherein N is the compound valence of the cation in the ligand source.

[0031] In another aspect, the present invention provides use of the above heat-stabilizing composition in improving the thermal stability of a polymer material, wherein the polymer material is selected from one or more of polyvinyl chloride and chlorinated polyvinyl chloride.

[0032] In another aspect, the present invention provides a polymer material composition, comprising 100 parts by weight of a polymer material and 1 to 5 parts by weight of the above-mentioned thermally stable composition;

[0033] The polymer material is selected from one or more of polyvinyl chloride and chlorinated polyvinyl chloride.

[0034] According to the polymer material composition of the present invention, preferably, the polymer material composition further comprises 10 to 50 parts by weight of light calcium carbonate and 1 to 5 parts by weight of an acrylic ester copolymer.

[0035] In another aspect, the present invention provides a method for preparing the above polymer material composition, comprising the following steps:

[0036] The raw materials including the polymer material and the heat-stabilizing composition are plasticized on a twin-roll plasticizer to obtain a polymer material composition.

[0037] The heat-stabilizing composition of the present invention contains a bimetallic complex of a specific structure, which can be combined with an antioxidant, a lubricant and an auxiliary stabilizer to effectively improve the thermal stability of polyvinyl chloride. After the heat stabilizer of the present invention is added to polyvinyl chloride, the equilibrium torque is small, which can reduce the power consumption in the preparation process, reduce the cost, and has significant economic benefits. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0039] <Heat-stable composition>

[0040] The heat-stable composition of the present invention comprises a bimetallic complex, an antioxidant, a lubricant and an auxiliary stabilizer. The heat stabilizer of the present invention does not contain calcium-zinc heat stabilizers such as zinc stearate, thereby improving the heat stability of the heat-stable composition. Preferably, the heat-stable composition of the present invention consists of a bimetallic complex, an antioxidant, a lubricant and an auxiliary stabilizer.

[0041] The central atoms of the bimetallic complex of the present invention are rare earth elements and transition metal elements, and the ligands of the bimetallic complex are shown in formula (I).

[0042] Preferably, the rare earth element is selected from one or more of lanthanum, neodymium, europium, and ytterbium. More preferably, the rare earth element is selected from one or more of lanthanum, europium, and ytterbium. Most preferably, the rare earth element is lanthanum.

[0043] The transition metal element is selected from one or more of aluminum, zinc, magnesium, tin and nickel. Preferably, the transition metal element is selected from one or more of nickel, zinc and tin. More preferably, the transition metal element is zinc.

[0044] Preferably, the central atom of the bimetallic complex is selected from one of the following compositions: (A) lanthanum and aluminum; (B) neodymium and magnesium; (C) europium and nickel; (D) lanthanum and zinc; (E) ytterbium and tin. More preferably, the central atom of the bimetallic complex is selected from one of the following compositions: (C) europium and nickel; (D) lanthanum and zinc; (E) ytterbium and tin. Most preferably, the central atom of the bimetallic complex is lanthanum and zinc.

[0045] The ligand of the bimetallic complex is shown in formula (I):

[0046]

[0047] Wherein, R1 and R2 are independently selected from C1-C6 alkyl groups; preferably, R1 and R2 are independently selected from C1-C3 alkyl groups; more preferably, R1 and R2 are both ethyl groups.

[0048] R1 and R2 may be the same or different. Preferably, R1 and R2 are the same.

[0049] The alkyl group may be a straight chain alkyl group or a branched chain alkyl group. Preferably, the alkyl group is a straight chain alkyl group.

[0050] Examples of C1-C6 alkyl groups include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, methylpropyl, dimethylethyl, pentyl, methylbutyl, dimethylpropyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, and ethylbutyl.

[0051] According to one embodiment of the present invention, the ligand is a diethyldithiocarbamate group.

[0052] The bimetallic complex of the present invention can be prepared by the following method: reacting a solution containing a rare earth element source, a transition metal element source and a ligand source to obtain the bimetallic complex.

[0053] The rare earth element source may be a rare earth salt substance, such as rare earth acetate.

[0054] The transition metal element source may be a transition metal salt substance, such as a transition metal chloride.

[0055] The anion of the ligand source is shown in formula (II):

[0056]

[0057] Wherein, R3 and R4 are independently selected from C1-C6 alkyl groups; preferably, R3 and R4 are independently selected from C1-C3 alkyl groups; more preferably, R3 and R4 are both ethyl groups.

[0058] R3 and R4 may be the same or different. Preferably, R3 and R4 are the same.

[0059] The alkyl group may be a straight chain alkyl group or a branched chain alkyl group. Preferably, the alkyl group is a straight chain alkyl group.

[0060] Examples of C1-C6 alkyl groups include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, methylpropyl, dimethylethyl, pentyl, methylbutyl, dimethylpropyl, ethylpropyl, hexyl, methylpentyl, dimethylbutyl, and ethylbutyl.

[0061] The cation of the ligand source can be a metal ion; preferably an alkali metal ion. In certain embodiments, the cation of the ligand source is a sodium ion or a potassium ion.

[0062] According to one embodiment of the present invention, the ligand source is sodium diethyldithiocarbamate.

[0063] The molar ratio of the rare earth element in the rare earth element source, the transition metal element in the transition metal element source, and the ligand source is 1: (0.5-2): (3 / N-7 / N); preferably 1: (0.8-1.5): (4 / N-6 / N); more preferably 1: (1-1.2): (5 / N-6 / N). N is the valence of the cation in the ligand source. When the cation in the ligand source is an alkali metal ion, N is 1, and the molar ratio of the rare earth element in the rare earth element source, the transition metal element in the transition metal element source, and the ligand source is 1: (0.5-2): (3-7); preferably 1: (0.8-1.5): (4-6); more preferably 1: (1-1.2): (5-6).

[0064] The content of the bimetallic complex is 0.5 to 2 parts by weight, preferably 0.8 to 1.5 parts by weight, and more preferably 1.0 to 1.2 parts by weight. This helps to improve the thermal stability of the polymer material and reduce the equilibrium torque.

[0065] The antioxidant of the present invention can be selected from one or more of antioxidant 1010, antioxidant 215, antioxidant 168, antioxidant 1076, antioxidant 5057, antioxidant 626, and antioxidant DLTP; preferably, the antioxidant is selected from one or more of antioxidant 1010, antioxidant 215, and antioxidant 168; more preferably, the antioxidant is antioxidant 1010.

[0066] The content of the antioxidant is 0.05 to 1 part by weight, preferably 0.2 to 0.8 part by weight, and more preferably 0.5 to 0.6 part by weight.

[0067] The lubricant of the present invention can be selected from one or more of stearic acid, polyethylene wax, oxidized polyethylene wax, Fischer-Tropsch wax, and monoglyceride. In certain embodiments, the lubricant is a composition of polyethylene wax and oxidized polyethylene wax. The mass ratio of polyethylene wax to oxidized polyethylene wax can be 0.6:(0.3-0.7); preferably 0.6:(0.5-0.6). In other embodiments, the lubricant is a composition of polyethylene wax and monoglyceride. The mass ratio of polyethylene wax to monoglyceride can be 0.6:(0.3-0.7); preferably 0.6:(0.4-0.5). In yet other embodiments, the lubricant is a composition of oxidized polyethylene wax and Fischer-Tropsch wax. The mass ratio of oxidized polyethylene wax to Fischer-Tropsch wax is 0.6:(0.4-0.8); preferably 0.6:(0.6-0.7).

[0068] The content of the lubricant is 0.5 to 2 parts by weight, preferably 0.8 to 1.5 parts by weight, and more preferably 1 to 1.2 parts by weight.

[0069] The auxiliary stabilizer of the present invention is selected from one or more of phosphite, dipentaerythritol ester, epoxy soybean oil, dibutyl maleate (DBM), dibenzoylmethane, and hydrotalcite. In certain embodiments, the auxiliary stabilizer is a composition of epoxy soybean oil and dibutyl maleate. The mass ratio of epoxy soybean oil to dibutyl maleate is 0.2:(0.05-0.4); preferably 0.2:(0.2-0.3). In other embodiments, the auxiliary stabilizer is a composition of dipentaerythritol ester and hydrotalcite. The mass ratio of dipentaerythritol ester to hydrotalcite is 0.3:(0.2-0.5); preferably 0.3:(0.3-0.4). In still other embodiments, the auxiliary stabilizer is a composition of phosphite and dibutyl maleate. The mass ratio of phosphite to dibutyl maleate can be 0.2:(0.1-0.5); preferably 0.2:(0.2-0.3).

[0070] The content of the auxiliary stabilizer is 0.1 to 0.9 parts by weight, preferably 0.3 to 0.7 parts by weight, and more preferably 0.5 to 0.6 parts by weight.

[0071] According to a preferred embodiment of the present invention, the heat-stabilizing composition includes 0.9 to 1.1 parts by weight of a bimetallic complex, 0.3 to 0.6 parts by weight of an antioxidant 1010, 0.5 to 0.7 parts by weight of a polyethylene wax, 0.3 to 0.5 parts by weight of a monoglyceride, 0.2 to 0.4 parts by weight of a dipentaerythritol ester and 0.2 to 0.4 parts by weight of a hydrotalcite.

[0072] The components of the heat-stable composition described above cooperate with each other, so that the heat-stable composition has an excellent effect of improving the thermal stability of polyvinyl chloride, has a smaller equilibrium torque, reduces energy consumption during processing, and reduces costs.

[0073] <Method for preparing heat-stable composition>

[0074] The preparation method of the heat-stable composition of the present invention comprises the following steps: mixing a bimetallic complex, an antioxidant, a lubricant and an auxiliary stabilizer to obtain a heat-stable composition. The selection and dosage of the bimetallic complex, the antioxidant, the lubricant and the auxiliary stabilizer are as described above and will not be repeated here. The mixing can be carried out in a high-speed mixer. The mixing time can be 0.2 to 5 minutes; preferably 0.5 to 3 minutes; more preferably 1 to 2 minutes.

[0075] In some embodiments, the method further comprises the step of preparing a bimetallic complex: reacting a solution containing a rare earth element source, a transition metal element source and a ligand source under the conditions that the initial pH of the reaction system is 6 to 9 and the temperature is 45 to 80° C. to obtain a bimetallic complex. The selection and dosage of the rare earth element source, the transition metal element source and the ligand source are as described above and will not be repeated here.

[0076] The solvent in the solution containing the rare earth element source, the transition metal element source and the ligand source can be a small molecule alcohol substance, or a mixture of a small molecule alcohol substance and water. Preferably, the small molecule alcohol substance is a small molecule monohydric alcohol; for example, methanol, ethanol, propanol, isopropanol, butanol, isobutanol. According to one embodiment of the present invention, the solvent is ethanol. According to another embodiment of the present invention, the solvent is ethanol and water. Based on 0.1 mol of the rare earth element source, the amount of the solvent can be 200 to 700 mL; preferably 300 to 500 mL.

[0077] The initial pH of the reaction system is 6 to 9, preferably 6.5 to 8.5, and more preferably 7.5 to 8. A pH adjuster may be used to adjust the initial pH of the reaction system. The pH adjuster may be an alkali metal hydroxide, such as sodium hydroxide or potassium hydroxide. The alkali metal hydroxide may be used in the form of a solution. The concentration of the alkali metal hydroxide solution may be 0.05 to 0.3 mol / L, and preferably 0.1 to 0.2 mol / L.

[0078] The reaction temperature is 45 to 80°C, preferably 50 to 70°C, and more preferably 60 to 65°C.

[0079] The reaction time may be 1 to 8 hours, preferably 2 to 7 hours, and more preferably 4 to 5 hours.

[0080] The reaction may be carried out under stirring.

[0081] According to one embodiment of the present invention, at the reaction temperature, an alkali metal hydroxide solution is added to a solution containing a rare earth element source, a transition metal element source and a ligand source to make the initial pH value of the reaction system 6 to 9, and then stirring is continued for 1 to 8 hours.

[0082] Specifically, the method further comprises the following steps: filtering the reaction product obtained by the reaction to obtain a solid product, washing the solid product and drying it to obtain a bimetallic complex.

[0083] <Application of heat-stable composition>

[0084] The heat-stable composition of the present invention can effectively improve the thermal stability of polymer materials such as polyvinyl chloride. Therefore, the present invention provides the use of the above-mentioned heat-stable composition in improving the thermal stability of polymer materials. The polymer material is selected from one or more of polyvinyl chloride and chlorinated polyvinyl chloride. Preferably, the polymer material is polyvinyl chloride.

[0085] <Polymer material composition and preparation method thereof>

[0086] The polymer material composition of the present invention comprises a polymer material and a heat-stabilizing composition. The polymer material is selected from one or more of polyvinyl chloride and chlorinated polyvinyl chloride; preferably, the polymer material is polyvinyl chloride. The heat-stabilizing composition is as described above and will not be described in detail here.

[0087] Based on 100 parts by weight of the polymer material, the amount of the heat stabilizing composition is 1 to 5 parts by weight, preferably 2 to 4 parts by weight, and more preferably 3 to 4 parts by weight.

[0088] Preferably, the polymer material composition further comprises light calcium carbonate and acrylic acid ester copolymer. The acrylic acid ester copolymer can also be referred to as a processing aid ACR.

[0089] The amount of light calcium carbonate used is 10 to 50 parts by weight, preferably 20 to 40 parts by weight, and more preferably 30 to 35 parts by weight.

[0090] The amount of the acrylic copolymer used is 1 to 5 parts by weight, preferably 2 to 4 parts by weight, and more preferably 3 to 4 parts by weight.

[0091] The preparation method of the polymer material composition comprises the following steps: plasticizing the raw materials including the polymer material and the heat-stabilizing composition on a double-roll plasticizer to obtain the polymer material composition.

[0092] The plasticizing time may be 1 to 8 minutes, preferably 2 to 6 minutes, and more preferably 3 to 4 minutes.

[0093] The roller temperature may be 150 to 210°C; preferably 160 to 200°C; more preferably 180 to 190°C.

[0094] The roller distance may be 0.5 to 5 mm, preferably 0.8 to 3 mm, and more preferably 1 to 1.5 mm.

[0095] Here are the raw materials:

[0096] The acrylic copolymer (processing aid ACR) is ACR 401.

[0097] Preparation Examples 1 to 5

[0098] Dissolve 0.1 mol of rare earth acetate in 100 mL of ethanol to obtain a rare earth element source solution. Dissolve 0.1 mol of transition metal chloride in 100 mL of ethanol to obtain a transition metal element source solution. Dissolve 0.5 mol of sodium diethyldithiocarbamate in 200 mL of ethanol to obtain a ligand source solution.

[0099] The rare earth element source solution, transition metal element source solution and ligand source solution are placed in a round-bottom flask, and a sodium hydroxide solution with a concentration of 0.1 mol / L is added to the round-bottom flask at a temperature of 60°C and under stirring until the pH of the reaction system is 7.5, and then stirring is continued for 5 hours to obtain a reaction product. The reaction product is filtered to obtain a solid product. The solid product is washed and dried to obtain a bimetallic complex.

[0100] The selection of rare earth acetate and transition metal chloride is shown in Table 1.

[0101] Table 1

[0102]

[0103] Comparative Preparation Example 1

[0104] 0.2 mol of lanthanum acetate was dissolved in 200 mL of ethanol to obtain a rare earth element source solution. 0.5 mol of sodium diethyldithiocarbamate was dissolved in 200 mL of ethanol to obtain a ligand source solution.

[0105] The rare earth element source solution and the ligand source solution are placed in a round-bottom flask, and a sodium hydroxide solution with a concentration of 0.1 mol / L is added to the round-bottom flask at a temperature of 60°C and under stirring until the pH of the reaction system reaches 7.5, and then stirring is continued for 5 hours to obtain a reaction product. The reaction product is filtered to obtain a solid product. The solid product is washed and dried to obtain a rare earth complex.

[0106] Comparative Preparation Example 2

[0107] 0.2 mol of aluminum chloride was dissolved in 200 mL of ethanol to obtain a transition metal source solution. 0.5 mol of sodium diethyldithiocarbamate was dissolved in 200 mL of ethanol to obtain a ligand source solution.

[0108] The transition metal element source solution and the ligand source solution are placed in a round-bottom flask, and a sodium hydroxide solution with a concentration of 0.1 mol / L is added to the round-bottom flask at a temperature of 60°C and under stirring until the pH of the reaction system is 7.5, and then stirring is continued for 5 hours to obtain a reaction product. The reaction product is filtered to obtain a solid product. The solid product is washed and dried to obtain a transition metal complex.

[0109] Example 1

[0110] 0.6 parts by weight of the bimetallic complex obtained in Preparation Example 1, 0.3 parts by weight of antioxidant 1010, 0.8 parts by weight of stearic acid and 0.3 parts by weight of phosphite were mixed in a high-speed mixer for 1 minute to obtain a heat-stable composition.

[0111] Example 2

[0112] 0.6 parts by weight of the bimetallic complex obtained in Preparation Example 2, 0.2 parts by weight of antioxidant 215, 0.6 parts by weight of polyethylene wax, 0.4 parts by weight of oxidized polyethylene wax and 0.3 parts by weight of dipentaerythritol ester were mixed in a high-speed mixer for 1 minute to obtain a heat-stable composition.

[0113] Example 3

[0114] 0.8 weight part of the bimetallic complex obtained in Preparation Example 3, 0.3 weight part of antioxidant 168, 0.6 weight part of polyethylene wax, 0.6 weight part of oxidized polyethylene wax, 0.2 weight part of epoxy soybean oil and 0.2 weight part of dibutyl maleate (DBM) were mixed in a high-speed mixer for 1 min to obtain a heat-stable composition.

[0115] Example 4

[0116] 1.0 part by weight of the bimetallic complex obtained in Preparation Example 4, 0.5 part by weight of antioxidant 1010, 0.6 part by weight of polyethylene wax, 0.4 part by weight of monoglyceride, 0.3 part by weight of dipentaerythritol ester and 0.3 part by weight of hydrotalcite were mixed in a high-speed mixer for 1 minute to obtain a heat-stable composition.

[0117] Example 5

[0118] 1.2 parts by weight of the bimetallic complex obtained in Preparation Example 5, 0.5 parts by weight of antioxidant 168, 0.6 parts by weight of polyethylene wax, 0.6 parts by weight of Fischer-Tropsch wax, 0.2 parts by weight of phosphite and 0.2 parts by weight of dibutyl maleate (DBM) were mixed in a high-speed mixer for 1 minute to obtain a heat-stable composition.

[0119] Comparative Example 1

[0120] The same procedures as in Example 1 are followed except that the bimetallic complex obtained in Preparation Example 1 is replaced by the rare earth complex obtained in Comparative Preparation Example 1.

[0121] Comparative Example 2

[0122] Except that the bimetallic complex obtained in Preparation Example 1 is replaced by the transition metal complex obtained in Comparative Preparation Example 2, the rest is the same as Example 1.

[0123] Examples 6 to 10 and Comparative Examples 3 to 5

[0124] A raw material consisting of 100 parts by weight of polyvinyl chloride, 30 parts by weight of light calcium carbonate, 3 parts by weight of an acrylic copolymer and 3 parts by weight of a heat-stabilizing composition (if any) is mixed and then plasticized for 3 minutes on a two-roll plasticizer. The roller temperature of the two-roll plasticizer is 180° C. and the roller distance is 1 mm.

[0125] The selection of heat-stabilizing compositions is shown in Table 2.

[0126] Table 2

[0127]

[0128] Experimental example

[0129] 1. Torque rheology experiment

[0130] Mixed samples containing polyvinyl chloride were prepared according to the composition of the raw materials in Examples 6 to 10 and Comparative Examples 3 to 5. 70 g of the mixed sample was taken as a sample to conduct a torque rheology experiment on a Haake rheometer, with the torque rheology temperature set to 185°C and the speed set to 50 r / min. The experimental results are shown in Table 3.

[0131] Table 3. Torque rheological results

[0132]

[0133] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A thermally stable composition, characterized in that The heat-stabilizing composition comprises 0.5 to 2 parts by weight of a bimetallic complex, 0.05 to 1 parts by weight of an antioxidant, 0.5 to 2 parts by weight of a lubricant, and 0.1 to 0.9 parts by weight of an auxiliary stabilizer; The central atoms of the bimetallic complex are rare earth elements and transition metal elements, and the ligands of the bimetallic complex are as shown in formula (I); The transition metal element is selected from one or more of aluminum, zinc, magnesium, tin and nickel; Wherein, R1 and R2 are independently selected from C1 to C6 alkyl groups; The auxiliary stabilizer is selected from one or more of phosphites, dipentaerythritol esters, epoxy soybean oil, dibutyl maleate, dibenzoylmethane, and hydrotalcite.

2. The heat-stable composition according to claim 1, characterized in that The rare earth element is selected from one or more of lanthanum, neodymium, europium and ytterbium.

3. The heat-stable composition according to claim 1, characterized in that The central atom is selected from one of the following compositions: (A) lanthanum and aluminum; (B) Neodymium and magnesium; (C) europium and nickel; (D) lanthanum and zinc; (E) Ytterbium and tin.

4. The heat-stable composition according to claim 1, characterized in that The antioxidant is selected from one or more of antioxidant 1010, antioxidant 215, antioxidant 168, antioxidant 1076, antioxidant 5057, antioxidant 626, and antioxidant DLTP; The lubricant is selected from one or more of stearic acid, polyethylene wax, oxidized polyethylene wax, Fischer-Tropsch wax, and monoglyceride.

5. The method for preparing a heat-stable composition according to any one of claims 1 to 4, characterized in that: The steps include: The dual metal complex, antioxidant, lubricant and auxiliary stabilizer are mixed to obtain a heat-stable composition.

6. The preparation method according to claim 5, characterized in that: The method further comprises the following steps: reacting a solution containing a rare earth element source, a transition metal element source and a ligand source under the conditions that the pH of the initial reaction system is 6 to 9 and the temperature is 45 to 80° C. to obtain a bimetallic complex; Wherein, the anion in the ligand source is as shown in formula (II): In formula (II), R3 and R4 are independently selected from C1 to C6 alkyl groups; The molar ratio of the rare earth element in the rare earth element source, the transition metal element in the transition metal element source, and the ligand source is 1:(0.5-2):(3 / N-7 / N); wherein N is the compound valence of the cation in the ligand source.

7. Use of the heat-stable composition according to any one of claims 1 to 4 or the heat-stable composition obtained by the preparation method according to any one of claims 5 to 6 in improving the thermal stability of polymer materials, wherein the polymer material is one or more selected from polyvinyl chloride and chlorinated polyvinyl chloride.

8. A polymer material composition, characterized in that: The polymer material composition comprises 100 parts by weight of a polymer material and 1 to 5 parts by weight of the thermally stable composition according to any one of claims 1 to 4; The polymer material is selected from one or more of polyvinyl chloride and chlorinated polyvinyl chloride.

9. The polymer material composition according to claim 8, characterized in that: The polymer material composition further comprises 10 to 50 parts by weight of light calcium carbonate and 1 to 5 parts by weight of an acrylic acid ester copolymer.

10. The method for preparing the polymer material composition according to claim 8 or 9, characterized in that: The steps include: The raw materials including the polymer material and the heat-stabilizing composition are plasticized on a twin-roll plasticizer to obtain a polymer material composition.

Citation Information

Patent Citations

  • A rare earth-transition metal bimetallic complex vulcanization accelerator of diethyldithiocarbamate

    CN104725432B

  • Rare earth-transition metal rubber vulcanization accelerator masterbatch and preparation method thereof

    CN109233029A